The making of modern cities: Examining long term urban land use characteristics in Melbourne - Hurley, J.; Groenhart, L.; Wood, Gavin; Meen, G. (2014)
This paper examines the nature of land use change over the long term in cities. It constitutes part of ongoing international research collaboration on the shaping of modern cities. The research seeks to understand the drivers of change, whether change is a gradual or discrete process, and the role of institutions in change. The central hypothesis of the research programme is that city structures change slowly due to path dependence that reflects inertia, increasing returns and transactions costs, but there are defining periods that produce major changes. These changes may flow from deliberate institutional interventions (such as infrastructure investment and policy change) or exogenous shocks (such as natural disaster, war, and technical change). We present the findings from a pilot study that employs property rate records and planning schemes to chart very long run changes in land use in the suburb of Carlton, Melbourne. These findings demonstrate the feasibility of this kind of research, and the potential importance of land ownership patterns to path dependence in urban development. If these findings were to be replicated more generally, they would suggest that an understanding of contemporary urban land use requires a more nuanced understanding of long run continuity and change in cities.